2020
DOI: 10.1101/2020.03.05.979682
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EYES ABSENT and TIMELESS integrate photoperiodic and temperature cues to regulate seasonal physiology inDrosophila

Abstract: Organisms possess photoperiodic timing mechanisms to anticipate variations in day length and temperature as the seasons progress. The nature of the molecular mechanisms interpreting and signaling these environmental changes to elicit downstream neuroendocrine and physiological responses are just starting to emerge. Here, we demonstrate that in Drosophila melanogaster, EYES ABSENT (EYA) acts as a seasonal sensor by interpreting photoperiodic and temperature changes to trigger appropriate physiological responses… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 73 publications
2
34
1
Order By: Relevance
“…Both properties are advantageous for a life in the north. A very recent study supports the role of TIM in dormancy of D. melanogaster (Abrieux et al, 2020). The authors showed that tim null mutants exhibit reduced incidence of reproductive dormancy in simulated winter conditions, while flies overexpressing tim show an increased incidence of reproductive dormancy even under long photoperiods.…”
Section: The Role Of the Clock In Photoperiodism And Diapause Needs Nmentioning
confidence: 72%
“…Both properties are advantageous for a life in the north. A very recent study supports the role of TIM in dormancy of D. melanogaster (Abrieux et al, 2020). The authors showed that tim null mutants exhibit reduced incidence of reproductive dormancy in simulated winter conditions, while flies overexpressing tim show an increased incidence of reproductive dormancy even under long photoperiods.…”
Section: The Role Of the Clock In Photoperiodism And Diapause Needs Nmentioning
confidence: 72%
“…The luciferase reporter was removed using MluI/XhoI restriction sites, and a 3XFLAG-6XHIS epitope was added in frame to the C terminus of the tim coding region. PhiC31 site-directed recombination 88 was used for transgenesis to generate yw; tim 0 ; tim(WT) (also described in 82 ). Plasmids were injected into yw fly embryos carrying attP sites on chromosome 3 (attP2) (BestGene, Chino Hills, CA).…”
Section: Lead Contactmentioning
confidence: 99%
“…In addition to investigations of circadian clock genes in plants, it has also been shown that temperature-dependent alternative splicing is essential for the regulation of circadian clock in Neurospora, Drosophila, tilapia and mice [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. These findings suggest that alternative splicing is a general mechanism of clock regulation.…”
Section: Regulation Of Gene Expression By Temperature-dependent Almentioning
confidence: 99%
“…In Drosophila, period (PER) and timeless (TIM) protein and mRNA products undergo daily fluctuations in relation to the circadian clock [ 66 , 71 , 73 , 74 , 77 ]. Majercak et al showed that temperature-dependent alternative splicing in the PER gene plays a key role in adaptation of a circadian clock to seasonally cold days (low temperatures and short day lengths) in Drosophila [ 73 ].…”
Section: Regulation Of Gene Expression By Temperature-dependent Almentioning
confidence: 99%